Biological control technology and application based on agricultural unmanned aerial vehicle (UAV) intelligent delivery of insect natural enemies (Trichogramma) carrier. Issue 7 (24th April 2021) - Zhan, Yilong; Chen, Shengde; Wang, Guobin; Fu, Jinwei; Lan, Yubin
Abstract: BACKGROUND: Agricultural pests and diseases affect grain yield and quality. In addition to the use of chemical agents, the biological control of diseases and insect pests has attracted more and more attention due to an urgent need for environmental protection. However, traditional operational methods do not integrate well with biological control technology. With the advantages of simple operation, low operating cost, high operating efficiency and wide application range, use of multirotor unmanned aerial vehicles (UAVs) in biological control is of great significance. RESULTS: An intelligent delivery system comprising an insect natural enemy ( Trichogramma ) capsule based on an M45 electric multirotor UAV was built to release Trichogramma ostriniae in corn fields under full autonomous mode. During operation, the M45 UAV can fly accurately in accordance with operational requirements; average deviation between the actual and planned routes was 0.24 m, the average flight speed was 9.18 m s −1 and the average altitude was 5.08 m. The effective coverage rate of natural enemies was 99.33% and the coverage redundancy was 36.75%. After delivery, an investigation into the field control effect showed an average control effect of 83.70%, which can result in effective pest control. CONCLUSION: A natural enemy carrier intelligent delivery system based on an M45 electric multirotor UAV was found to have good flight performance. In addition, natural enemies were evenly distributed, giving even coverage of the target fields. The system had a good control effect. © 2021 Society of Chemical Industry. Abstract : Coverage area of the capsule. The rectangular area formed by the dotted line represents the test field, and the circular area is the coverage area of the unit capsule. © 2021 Society of Chemical Industry.